Analysis of mental workload indicators among railway crossing guards in Yogyakarta City - Hariyono, Widodo; Afriansyah, Robert (Universitas Ahmad Dahlan, 2023)
Background: Mental workload is the workload which results from the performed works, is seen from the performed works, and develops cognitively (within mind). The mental activities are also dominated by the jobs with a high level of alertness, such as what is found among railway crossing guards. This study aims to analyze the mental workload indicators among railway crossing guards in Yogyakarta City. Method: The study was conducted using a qualitative descriptive approach. The guideline to conduct interviews and to measure mental workloads was NASA – TLX (National Aeronautics and Space Administration – Task Load Index), with the procedures consisting of weighting, rating, and calculation of mental workloads. The population was all of the railway crossing guards in Yogyakarta City consisting of as many as 32 respondents. Results: The results of the study showed that 26 respondents experienced a high level of mental workloads, 4 respondents experienced a moderately high level of mental workloads, and 2 respondents experienced an extremely high level of mental workloads (subjectively). Conclusion: The aspects of mental workloads elaborated in this study were Mental Demand (MD), Physical Demand (PD), Temporal Demand (TD), Performance (P), Frustration Level (FL), and Effort (E). The most influencing aspect on mental workloads of railway crossing guards was the Performance aspect, with a value of 5473, since this aspect required high responsibility for the job.